Komandorskīe ostrova na Tikhomʺ okeani︠e︡ / Izdanīe Gidrograficheskago D-ta M. M. 1883 goda - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1883)
Relief shown by hachures. Depths shown by soundings.; Title translation: Commander Islands in the Pacific. Published by the Hydrographic Department of the Admiralty in 1883.; Greenwich meridian.; Maps translations: Map of the Commander Islands (in the Bering Sea off the eastern coast of the Kamchatka peninsula). Compiled from various maps and notes and checked on site by Clipper "Vestnik" in 1882 -- Plan of the Staraya Gavan on Bering Island. According to the survey by the cruiser "Africa" in 1882 -- Plan of the harbor on Bering Island according to the survey of the clipper Strelok in 1881 -- Plan Mednyy Island from the map of Captain Zandman supplied to the clipper "Strelok" in 1881 -- Plan of Peschanaya Bay on the eastern coast of Mednyy Island. According to survey by the cruiser "Africa" in 1882 -- Plan of Harbor of Mednyy Island from the map of Captain Zandman 1882.; Maps: Karta Komandorskikh ostrovov (v Beringovom mori︠e︡ u O-go berega poluostr. Kamchatki). Sostavlena po raznym kartam i zapiskam i provi︠e︡rena na mi︠e︡sti︠e︡ Kliperom "Vi︠e︡stnik" v 1882 g. -- Plan Staroĭ gavani na ostrovi︠e︡ Beringa. Po glazomi︠e︡rnoĭ sʺëmki︠e︡ proizvedennoĭ s kreĭsera "Afrika" v 1882 godu -- Plan gavani na o-vi︠e︡ Bering po menzulʹnoĭ sʺëmki︠e︡ klipera Stri︠e︡lok v 1881 g. -- Plan ostrov Mi︠e︡dnyĭ s karty Kapitana Zandmana dostavlennyĭ kliperom "Strëlok" v 1881 godu -- Plan bukhty Peschannoĭ na vostochnom beregu o. Mi︠e︡dnyĭ. Po glazomi︠e︡rnoĭ sʺëmki︠e︡ kreĭsera "Afrika" v 1882 goda -- Plan gavani na o-vi︠e︡ Mi︠e︡dnom s karty Kap. Zandmana 1882 goda.; "No. 300" -- bottom right margin Grayscale;